The Influence of on the Job Training and Supervisor Guidance on Trainees Work Readiness At LV8 Resort Hotel Canggu - Ni Wayan Roospitasari; Wayan Suryathi; Ni Ketut Suciani (Journal of Management and Social Sciences, 2026)
This study aims to analyze the influence of On-the-Job Training and Supervisor Guidance on trainees’ Work Readiness at LV8 Resort Hotel Canggu. Work readiness is a crucial issue in the hospitality industry because hotel service quality strongly depends on human resources who are able to understand work procedures, adapt to organizational culture, communicate professionally, and demonstrate discipline, responsibility, and service-oriented behavior. This study employed a quantitative approach with an associative research design. The research population consisted of all trainees participating in the workplace training program at LV8 Resort Hotel Canggu during the June–December 2025 period, totaling 61 respondents. A total sampling technique was applied, meaning that the entire population was used as the research sample. Data were collected using a five-point Likert-scale questionnaire and analyzed through validity testing, reliability testing, classical assumption testing, multiple linear regression, t-test, F-test, and coefficient of determination analysis. The findings reveal that On-the-Job Training has a positive and significant effect on Work Readiness, with a beta value of 0.538, t-value of 4.968, and p-value of 0.000. Supervisor Guidance also has a positive and significant effect on Work Readiness, with a beta value of 0.238, t-value of 2.201, and p-value of 0.032. Simultaneously, both variables significantly influence trainees’ work readiness, as indicated by an F-value of 13.958 and a p-value of 0.000. The Adjusted R Square value of 0.302 indicates that On-the-Job Training and Supervisor Guidance explain 30.2% of the variation in Work Readiness, while the remaining 69.8% is influenced by other factors outside the research model. These findings confirm that direct workplace experience and supervisor guidance are essential factors in developing hotel trainees’ readiness for professional employment. The practical implication of this study suggests that hotel management should improve the quality of OJT implementation, strengthen periodic evaluation, and optimize the role of supervisors as mentors so that trainees can develop stronger competence, confidence, adaptability, and readiness to enter the professional hospitality workforce.